2012
DOI: 10.1002/clen.201200045
|View full text |Cite
|
Sign up to set email alerts
|

A Wetland Network Design for Water Allocation Based on Environmental Flow Requirements

Abstract: Excessive water use with economic development has led to the shortage of environmental flow requirements (EFRs) for different wetlands in the past years, a number of wetlands become degraded or disappeared. A suitable water allocation used for wetland restoration has become focus in the field. This article presents a wetland network design approach to achieve the objective of water allocation. First, a wetland network was designed by linking linear wetlands (as edges) and patch wetlands (as nodes), the EFRs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For example, large‐scale land development and infrastructure construction projects have changed surface loss potentials, leading to significant changes in the generation and accumulation of runoff and ultimately affecting fluxes of materials to RLMSs (Julian, Wilgruber, de Beurs, Mayer, et al, 2015), with consequences for regional and even global biogeochemical cycles. Whilst past restoration and regulation efforts were often based on the idea that managing structural connectivity would lead to increased functional connectivity, that is not necessarily the case (Tischendorf & Fahrig, 2000; Yang & Cui, 2012). We argue that more attention should be paid to the restoration of both functional and structural connectivity and that the connectivity of water, sediments, and chemicals should be jointly assessed to ensure the integrated and sustainable management and improvement of ecosystem functions in RLMSs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, large‐scale land development and infrastructure construction projects have changed surface loss potentials, leading to significant changes in the generation and accumulation of runoff and ultimately affecting fluxes of materials to RLMSs (Julian, Wilgruber, de Beurs, Mayer, et al, 2015), with consequences for regional and even global biogeochemical cycles. Whilst past restoration and regulation efforts were often based on the idea that managing structural connectivity would lead to increased functional connectivity, that is not necessarily the case (Tischendorf & Fahrig, 2000; Yang & Cui, 2012). We argue that more attention should be paid to the restoration of both functional and structural connectivity and that the connectivity of water, sediments, and chemicals should be jointly assessed to ensure the integrated and sustainable management and improvement of ecosystem functions in RLMSs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 28 also tried to use a wetland network which is a methodology to divert saltwater to explain how to address the adverse effects of saltwater intrusion and aims to mitigate such intrusion. Yang et al 29 designed a wetland network by linking linear wetlands and patch wetlands, determined the water trade‐off between human use and wetland network and calculated the environmental flow requirement. Their results showed that the designed network with three new patch wetlands and water trade‐off scenarios made additional water available to wetlands.…”
Section: Previewmentioning
confidence: 99%
“…The shrinking of wetland area is closely related to the decrease of water resources in wetlands, and the atrophy of lake area is directly impacted by the shrinking of wetland area [3]. Therefore, it is of vital importance to study the water flow in lakes to find out the feasible measures for wetland conservation [1,4].…”
Section: Introductionmentioning
confidence: 99%